Foreign Trade Regimes and Economic Development: The Philippines. By Robert E. Baldwin. New York: Columbia University Press (Published by the National Bureau of Economic Research, New York). 165 Pp. (The Pakistan Development Review, 1976)
In line with the theme set out in its sister volumes, the book under review explores the anatomy of exchange control, the liberalization of exchange controls and the relationship of the exchange control system to growth for Philippines for the period from World War II to 1971. It makes searching probes-into how different commercial policies and exchange controls influenced growth, employment, resource allocation and income distribution. A great deal of attention is focused on the evaluation of attempts to liberalize the exchange controls. Fiscal and monetary measures are also accorded detailed treat¬ment commensurate with their importance.